Volcanism and Global Environmental Change - Schmidt, Anja (Cambridge University Press, 2015)
Cover; Half-title; Title page; Copyright information; Table of contents; List of contributors; Preface; Part One Large volume volcanism: origins, features and timing; 1 Large igneous provinces and explosive basaltic volcanism; 1.1 Introduction; 1.2 Mafic volcanic-derived clastic deposits; 1.2.1 Primary volcaniclastic deposits; 1.2.2 Reworked volcaniclastic and epiclastic deposits; 1.3 Spatial and temporal occurrence of mafic volcaniclastic deposits; 1.3.1 East Greenland, North Atlantic Igneous Province; 1.3.2 Emeishan large igneous province; 1.3.3 Siberian flood basalts
Description based upon print version of record
Keywords: Electronic books; Umweltveränderung; Vulkan; Vulkanismus